Language teacher professional curiosity: Understanding the drive for professional development - Mercer, Sarah; Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2024)
Teacher professional development (PD) has been shown to have numerous benefits, such as greater self-efficacy, higher motivation, and enhanced wellbeing (e.g., Kimura, 2014; Polin, 2023; Wang & Chen, 2022), and teaching additional languages is certainly no exception. However, the extent to which teachers are willing and able to engage in PD throughout their careers depends on many factors, some of which are related to the context in which they work, while others are reflective of their individual attributes such as attitudes, motivations, and personality. This paper focuses on the latter by reporting the findings of a study that examined language teacher professional curiosity (LTPC). The data were collected through semi-structured interviews from 6 Austrian and 6 Polish language teachers at different stages of their careers. Qualitative analysis allowed valuable insights into the nature of LTPC, curiosity-driven behaviors as well as factors influencing these behaviors. It also provided the basis for a tentative cyclic process model of LTPC in which interest and curiosity interact to produce a focus of curiosity, which is impacted by motivation, agency, autonomy, and social context, generating a drive for teacher behaviors in respect to their PD.